Greasing the inflammatory pathogenesis of viral pneumonias in diabetes. (5th January 2022) - Damen, Michelle S. M. A.; Alarcon, Pablo C.; Shah, Amy S.; Divanovic, Senad
Summary: Type 2 diabetes (T2D) and obesity are independent risk factors for increased morbidity and mortality associated with influenza and SARS‐CoV‐2 infection. Skewed cellular metabolism shapes immune cell inflammatory responsiveness and function in obesity, T2D, and infection. However, altered immune cell responsiveness and levels of systemic proinflammatory mediators, partly independent of peripheral immune cell contribution, are linked with SARS‐CoV‐2‐associated disease severity. Despite such knowledge, the role of tissue parenchymal cell‐driven inflammatory responses, and specifically those dominantly modified in obesity (e.g., adipocytes), in influenza and SARS‐CoV‐2 infection pathogenesis remain poorly defined. Whether obesity‐dependent skewing of adipocyte cellular metabolism uncovers inflammatory clades and promotes the existence of a 'pathogenic‐inflammatory' adipocyte phenotype that amplifies SARS‐CoV‐2 infection diseases severity in individuals with obesity and individuals with obesity and T2D has not been examined. Here, using the knowledge gained from studies of immune cell responses in obesity, T2D, and infection, we highlight the key knowledge gaps underlying adipocyte cellular functions that may sculpt and grease pathogenic processes associated with influenza and SARS‐CoV‐2 disease severity in diabetes.